2008
DOI: 10.1097/qad.0b013e32830ebcd4
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between genotypic predictions based on V3 sequences and phenotypic determination of HIV-1 tropism

Abstract: Genotypic predictions performed well in paired genotypic and phenotypic assessment of HIV-1 coreceptor usage. Multicenter studies analyzing the correlations between the genotypic determination of HIV-1 tropism and clinical response to CCR5 antagonists are needed to validate this approach in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
111
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(123 citation statements)
references
References 19 publications
7
111
2
2
Order By: Relevance
“…These figures are comparable with previous estimates [22,23,25,29]. Although the overall concordance with PTT was higher with an FPR of 5% than with an FPR of 10%, the difference was very small.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These figures are comparable with previous estimates [22,23,25,29]. Although the overall concordance with PTT was higher with an FPR of 5% than with an FPR of 10%, the difference was very small.…”
Section: Discussionsupporting
confidence: 91%
“…The aim of the present study was to explore the possibility of using proviral DNA for GTT, by comparing large series of both simultaneous plasma RNA and proviral DNA samples from patients with a viral load of 4500 copies/ mL, and current proviral DNA samples and stored plasma RNA samples collected from treated patients with a current viral load of o500 copies/mL. Several algorithms for coreceptor tropism prediction from the envelope V3 sequence have been developed and evaluated [22][23][24][25]. As the aim of the study was not to compare the performances of interpretation systems, analysis was restricted to one algorithm only, geno2pheno (http://coreceptor.bioinf.mpi-inf.mpg.de/index.php), which has demonstrated comparable performance to OTA and ESTA [9].…”
Section: Discussionmentioning
confidence: 99%
“…The "gold standard" for characterization of HIV-1 tropism is a recombinant virus phenotypic entry assay, but genotypic methods based on the V3 sequence could be easier. We have previously shown that the V3 genotype accurately predicts the phenotype of HIV-1 coreceptor usage for subtype B viruses (5,13). However, the V3-based genotypic algorithms could be unsuitable for predicting the tropism of non-B viruses because they were built using data sets of genotype-phenotype correlations from subtype B viruses (9).…”
mentioning
confidence: 99%
“…Two separate PCR amplifications were performed in parallel for each patient and pooled to prevent sampling bias of the assessed virus population. The V3 region from the env PCR product was bulk sequenced, blinded to the phenotype, as previously described (13). Bulk sequencing allows the detection of minor variants when present at a frequency of at least 20% in the viral population.…”
mentioning
confidence: 99%
“…In other studies, higher sensitivities could be found for the same genotypic algorithms (Chueca et al, 2009;Raymond et al, 2008). Geno2pheno presented sensitivities of 88-93.7% and specificity of 87%, and PSSM with sensitivities of 77% and specificity of 94%.…”
Section: Impact Of Hiv-1 Diversity In the Performance Of Genotypic Anmentioning
confidence: 65%